Psychoanalytic Perspectives on Puberty and Adolescents: The Inner World of Teenagers and their Parents - Diem-Wille, Gertraud (2021)
The book describes puberty as a time of tumultous transition from childhood to adulthood. The book describes the physical development along with the typically adolescent "state of mind". This constitutes for parents and teachers a difficult emotional task, although this development is also a quite "normal drama".